A Study of Areas Affected by the Burning of Waste Landfills in Samut Prakan Province with the ALOHA Model - Sunthonchotchuang, Chawaphon; Attaphan, Nareerat; Junkaew, Nutthapol (Journal of Applied Informatics and Technology, 2023)
The objective of this research was to study the areas affected by the burning of waste landfills in Samut Prakan Province using the ALOHA model. (1) the analysis from the atmospheric dispersion ALOHA model, exposed that Carbon Monoxide has spread covering the area of 6,151.23 rai. The outcome was later confirmed by photos taken from the THEOS satellite over the burning Praeksa landfill and areas covered with smoke on March 18, 2014 with the overall accuracy of 81.98 %. (2) The areas affected from the smoke were divided into 3 categories: buildings and structures, significant places, and areas of land use. Buildings and structures were most affected with the concentration over 3 ppm damaging 3,612 households. For the significant places, the places that has been most affected was found with the concentration over 1-2 ppm. 6 considerable places composed of 4 schools and 2 gas stations were damaged. The last thing was areas of land use, the areas of land use that have been most affected were found with the concentration over 1-2 ppm with a total area of 93,130 rai.